2021
DOI: 10.1590/fst.14520
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of ultrasound-assisted extraction of turkish propolis and characterization of phenolic profile, antioxidant and antimicrobial activity

Abstract: This study aimed to determine optimum conditions of the ultrasound assited extraction (UAS) parameters for different solvent types by using response surface methodology (RSM) and Box-Behnken design. The model parameters namely, time, temperature and ultrasound power significantly affected TPC value of the propolis extract (P < 0.05). The optimum process parameters were determined as 2.95 min, 58.61 °C and 615.26 W for ethanol, 3 min, 60°C and 580 W for dimethyl sulfoxide (DMSO), 3 min, 59 °C and 591 W for Prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 32 publications
2
16
0
2
Order By: Relevance
“…Also, propolis extract showed stronger antibacterial activity against the Gr+ bacteria (10 -26.5 mm) than the Gr-bacteria (6 -13.5 mm). Comparable results were found by Bakkaloglu et al (2021). They also reported that ethanol as an extraction solvent provided higher antimicrobial activity for the Turkish propolis extracts in comparison to propylene glycol, dimethyl sulfoxide, and distilled water.…”
Section: Antibacterial Effect Of Propolis Extractmentioning
confidence: 59%
See 1 more Smart Citation
“…Also, propolis extract showed stronger antibacterial activity against the Gr+ bacteria (10 -26.5 mm) than the Gr-bacteria (6 -13.5 mm). Comparable results were found by Bakkaloglu et al (2021). They also reported that ethanol as an extraction solvent provided higher antimicrobial activity for the Turkish propolis extracts in comparison to propylene glycol, dimethyl sulfoxide, and distilled water.…”
Section: Antibacterial Effect Of Propolis Extractmentioning
confidence: 59%
“…Bioactivity of propolis depends on many factors such as geography, season, plant resource, composition and concentration of phenolic compounds, and extraction methodology (Toreti et al, 2013;Rivero-Cruz et al, 2020;Bakkaloglu et al, 2021). It has been noted that Turkish propolis in particular with the presence of wide range of flavonoids (Coskun et al, 2018) and phenolics (Bakkaloglu et al, 2021) has an elevated antioxidant and antimicrobial activity (Ristivojevic et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The use of experimental design and, more specifically, response surface methodology is becoming increasingly common in the optimization of polyphenol extraction from natural products, and propolis is one of them [16][17][18].These chemometric tools are used by establishing a mathematical model that evaluates multiple parameters and their interactions using quantitative data, effectively optimizing complex extraction procedures, and thus reducing the number of experimental trials required [18,19].In this same approach, a Box-Behnken design (BBD)was applied to optimize extraction yield, total polyphenols and flavonoids, and antioxidant activity by using DPPH-IC 50 and FRAP-EC 50 tests from Moroccan propolis.…”
Section: Introductionmentioning
confidence: 99%
“…As metodologias convencionais (sólido-líquido) ainda são muito populares, mesmo com as desvantagens de possuírem baixo ren-dimento, serem demoradas, e modificarem as amostras após extração, devido a degradação ocasionada por oxidação, hidrólise e ionização. Dentre as mais comuns, podem ser citadas maceração, processamento de alta pressão, ultrassom, irradiação gama, fluido supercrítico, Soxhlet e micro-ondas (53,64).…”
Section: Resultsunclassified
“…Bakkaloglu e cols. (2021) estudaram os efeitos do uso de maceração dinâmica e extração por ultrassom, obtendo uma melhor extração de compostos fenólicos e capacidade antioxidante pelo método de ultrassom (64).…”
Section: Resultsunclassified